Prospective Evaluation of Atrial Fibrillation Risk in Type 2 Diabetes Comparing SGLT-2 Inhibitors and DPP-4 Inhibitors - Khan, Nasir; Khan , Amir; Umar, Zeeshan; Muhammad, Faiz; Abbas , Mohammad; Ahmed , Atizaz; Zarmina , Bibi; Ullah , Kaleem (Indus Journal of Bioscience Research, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a major risk factor of atrial fibrillation (AF). In particular, sodium glucose co-transporter-2 (SGLT2) inhibitors and dipeptidyl peptidase-4 (DPP4) inhibitors are often used to treat T2DM, and effects of these drugs on risk for AF are unknown. The goal of this study was to investigate if SGLT 2 inhibitor are associated with an increase in the incidence of new onset AF, as well as the incidence of cardiovascular outcomes, versus DPP4 inhibitors. Prospective cohort study was conducted at Lady Reading Hospital, Peshawar from July 2024 to December 2024 in 370 T2DM patients aged 40 to 75 years, started on SGLT2 inhibitors (n= 189) or DPP4 inhibitors (n= 181). Follow up was for 6 months and patients were followed up with regular electrocardiographic evaluation for the occurrence of new onset of AF. Other secondary outcomes were hospitalization for ischemic stroke and heart failure. Cox proportional hazards models and Kaplan-Meier survival analysis were used to assess AF risk and cardiovascular outcomes adjusting for confounders, including age, sex, hypertension and BMI. Results: New onset of AF incidence was significantly lower in SGLT-2 inhibitor group (p < 0.05) compared with DPP-4 inhibitor group. As well, SGLT-2 inhibitors also reduced the risk of hospitalization for heart failure or ischemic stroke in patients. The two groups had similar baseline characteristics. TAMP patients treated with SGLT 2 inhibitors had a reduced risk of new onset AF as well as more favorable cardiovascular outcomes compared to TAMP patients treated with DPP 4 inhibitors. These may suggest SGLT-2 inhibitors as a mechanism to suppress both the arrhythmic and cardiovascular manifestations of diabetes. The benefits here warrant further large-scale studies to confirm them.